Analisis Pengaruh Atraksi Wisata, dan Ancillary Service terhadap Minat Kunjung Ulang pada Objek Wisata Bukit Siguntang - Ramadhani, Suci Anggraini; Setiawan, Heri; Rini, Rini (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2021)
The purpose of the research is to identify the effect of a tourist attractions, tourist amenities, tourist accessibilities and ancillary services partially and simultaneously towards interest to revisit in Bukit Siguntang, Palembang. This research used a quantitative descriptive approach. This research used descriptive analysis and multiple linear regression analysis.. The sampling technique used in this research is non probability sampling with incidental sampling approach. The sample in this research were the visitors of Bukit Siguntang Palembang with 99 respondents. Based on the T test results, it has known that tourist attractions and ancillary services have positive and significant effect towards interest to revisit in Bukit Siguntang, while tourist amenities and tourist accessibilities have no significant effect on the tourists' revisiting interest. Based on the F test results, it has known that there is a simultaneously significant influence among tourist attractions, tourist amenities, tourist accessibilities and ancillary services to the tourists' revisiting interest. The better a tourist attraction have, the bigger tourists' revisiting interest will be at Bukit Siguntang Palembang.